Bagaimana Pola Asuh Orang Tua dan Kecerdasan Intrapersonal Menjelaskan Prestasi Belajar Siswa? - Fadhillah, Dilla; Novianti, Ersa (JURNAL PENDIDIKAN DASAR NUSANTARA, 2021)
The purpose of this study was to explore parenting styles with intrapersonal intelligence on student learning achievement in indonesian subjects. This research used a qualitative approach with a case study design. The subjects in this study were 15 grade III students at one of the Madrasah Ibtidaiyah (MI) in Tangerang City, teacher, and parents of students. Data collection techniques were carried out through interviews with students, teachers, and parents of students; filling out a questionnaire by students and parents of students; observation of the process of learning activities followed by students; and documentation of documents that support student achievement data. The research validation was carried out through the triangulation method. The results of this study indicate that parenting patterns that have an impact on high student achievement include a combination of democratic and authoritative parenting styles. Authoritarian parenting also explains student achievement, but in the moderate category. Permissive parenting tends to encourage students to have difficulties in facing problems, so that students achieve learning achievement in the low category. Student achievement is also directly proportional to the level of students' intrapersonal intelligence. The more students are able to recognize themselves, reflect on their actions, and control themselves, the more capable students are to achieve optimal learning achievement.